Molecular identification and phylogenetic analysis of Pseudoperonospora cubensis isolates in Peninsula Malaysia - Salati, Mansour; Meon, Sariah; Tan, Yee How; Wong, M. (Universiti Putra Malaysia Press, 2012)
Thirteen isolates of Pseudoperonospora cubensis, the causal agent of downy mildew, were collected from cucurbit fields in five states of the western part of Peninsular Malaysia during its growing season between November 2008 and March 2009. The host range of these isolates was determined previously using leaf disc assay and the results indicated that there were 12 pathotypes among these isolates. The objective of this study was to analyze the 13 isolates for phylogenetic relationship using internal transcribed spacers (ITS) of ribosomal DNA (rDNA) and mitochondrial COX-II regions. A high sequence similarity among the 13 isolates and similar sequences from GenBank were detected in ITS (>99%) and COX-II (>98%) regions. Phylogenetic analysis of the 13 isolates based on Minimum Evolution method performed on ITS and COX-II regions revealed five and three groupings, respectively. However, no relationship was found between the phylogenetic groupings using both genes and pathotypes in this study.